Code-choice on Twitter: How stance-taking and linguistic accommodation reflect the identity of polyglossic Egyptian users - Mashhour, Sahar (AUC Knowledge Fountain, 2016)
This study examines the online identity of polyglossic Egyptian users of Twitter. It is descriptive and exploratory utilizing a qualitative design with some frequency count which adds descriptive data. Data were collected using a Discourse Completion Task (DCT) where the participants were presented with a number of tweets and were asked to type another tweet in response to each. The findings from the study suggest that polyglossic Egyptians, those who are proficient in English as well as Arabic, exhibited an assertive identity on Twitter. This identity was constructed through the choice of code, the linguistic accommodation to the tweet authors, and the stance they took. Polyglossic Egyptians were found to use English more than any other code, followed by Arabizi, and then Arabic. They linguistically accommodated the tweet authors in their replies to some extent by choosing the same code in replying as that used in the original tweet. Further, and using Du Bois’ (2007) stance triangle framework, it was also found that they expressed their (dis)alignment quite bluntly by taking an epistemic stance achieved through the use of boosters (very few hedges were used), sarcasm, simple present tense (to express an opinion as if stating a fact), and modals (to offer advice). By doing that, polyglossic Egyptians were found to be assertive in expressing their opinions, often showing themselves as informative, superior people who are guided by facts about topics rather than feelings.